Jewish Ceremony for Newborn Girls : the Torah's Covenant Affirmed. - Siegel, Sharon R. (Brandeis, 2014)
This engaging book offers the first in-depth analysis of the history, philosophy, and social trends that underpin modern welcoming ceremonies for newborn girls in the Jewish community. Sharon R. Siegel traces the arc of these ceremonies from their emergence in the 1970s until today. She also delves into the history of how Jewish girls have been named over the centuries and explores how this history can shape contemporary welcoming practices. Siegel builds on the notion that modern ceremonies should focus on a newborn girl's entry into the covenant between God and Israel and examines cl.
I. Naming and welcoming. Traditional Ashkenazic naming practices for girls -- A first and only naming -- New modern practices for baby girls -- II. covenant. Women and covenant -- The conflation of covenant and circumcision -- A central covenantal ritual for girls -- Conveying the covenantal theme -- III. A tradition of customs. Ceremonies for newborn girls as developing customs -- An eighth-day ceremony for newborn Jewish girls.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Brit bat -- History; RELIGION -- Judaism -- General; Brit bat; SOCIAL SCIENCE / General; Electronic books; History